Diametric structure in a community of shrub-tree Caatinga, municipality of Floresta, state of Pernambuco, Brazil - Lima, Robson Borges de; Ferreira, Rinaldo Luiz Caraciolo; da Silva, José Antônio Aleixo; de Oliveira, Cinthia Pereira; da Silva, Gilson Fernandes; Alves Júnior, Francisco Tarcísio (Floresta, 2018)
This study aimed to analyze the diametric structure of the stand and of five species of highest importance value for a Caatinga area, located in the municipality of Floresta, state of Pernambuco, Brazil. The work was developed from 40 sample units of 400 m² each, systematically allocated. All individuals with tree circumference at the base (0.30 m) greater than or equal to 6 cm were measured. The "q" quotient of De Liocourt was used to verify discrepancies between recruitment rates and mortality. We reported that, for the studied area, the species Poincianella bracteosa(Tul.) L. P. Queiroz, Mimosa ophthalmocentra Mart. ex Benth., Aspidosperma pyrifolium Mart., Myracrodum urundeuva(Engl.) Fr. All., and Bauhinia cheilanta(Bong). Steud represented 77.25% of the total density sampled. The diametric distributions indicated that regeneration occurs continuously. Through the "q" quotient, it can be inferred that, for the study stand, Myracrodum urundeuva and Poincianella bracteosa, the individual’s mortality has been compensated by recruitment in different diameter classes. However, the diametrical structure for Mimosa ophthalmocentra, Aspidosperma pyrifolium, and Bauhinia cheilanta indicated problems of maintenance and development for these species.